Personality traits, parenting styles and cyber aggression among university students in Johor, Malaysia - Mah, Yan Zhou; Hasbullah, Muslihah (Human Resource Management Academic Research Society, 2023)
Malaysian cyberspace has been the target of cyber aggression in recent years, and similar issue has reportedly occurred in many other nations as well. The emergence of cyber-aggressive behaviour has been linked to some personality traits and parenting practises. The objective of this study was to determine the relationship of personality traits, parenting styles and cyber aggression among university students in Johor. A total of 204 undergraduates were participated in this study. The data were collected through a self-administered questionnaire. Big Five Inventory (BFI) by John et al. (1991) was used to determine the personality traits, Egna Minnen Betraffande Uppfostran- Short Form (S-EMBU) from Arrindell et al. (1999) was used to measure parenting style and Cyber-Aggression Scale (CYB-AGS) by Buelga et al (2020) was used to measure cyber aggression. Result shown a moderate level of cyber aggression among respondents. The traits of extraversion (r=0.237, p≤0.01), parenting styles of rejection (r=0.639, p≤0.01), emotional warmth (r=0.173, p≤0.05) and overprotection (r=0.490, p≤0.01) were positively and significantly correlated with cyber aggression. Traits of agreeableness (r=-0.130, p≥0.05), conscientiousness (r=-0.079, p≥0.05) and neuroticism (r=-0.062, p≥0.05) were not significant but negatively correlated with cyber aggression. Significant gender difference was found in cyber aggression among the respondents (t=3.563, p≤0.001). Lastly, extraversion traits, and parenting styles of rejection were the significant predictors of cyber aggression among the respondents. This study highlights on the understanding of different personality traits and parenting style that predict how young adults respond to cyber aggression.